2021
DOI: 10.1038/s41525-021-00213-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation analysis on C-reactive protein among Ghanaians suggests molecular links to the emerging risk of cardiovascular diseases

Abstract: Molecular mechanisms at the intersection of inflammation and cardiovascular diseases (CVD) among Africans are still unknown. We performed an epigenome-wide association study to identify loci associated with serum C-reactive protein (marker of inflammation) among Ghanaians and further assessed whether differentially methylated positions (DMPs) were linked to CVD in previous reports, or to estimated CVD risk in the same population. We used the Illumina Infinium® HumanMethylation450 BeadChip to obtain DNAm profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Second, in the present study, we have demonstrated that, above a cut-off of 20 mg/L, CRP levels become inversely associated with epigenetic age acceleration. This might be a “paradoxical” statistical artifact (due to the six out of 72 subjects falling in this group), but, in our opinion, because of the association of epigenetic loci in its gene with inflammation and CVD [ 37 ], CRP might become the “perpetrator and victim” of the same obesity-related DNA destabilization previously described [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 94%
“…Second, in the present study, we have demonstrated that, above a cut-off of 20 mg/L, CRP levels become inversely associated with epigenetic age acceleration. This might be a “paradoxical” statistical artifact (due to the six out of 72 subjects falling in this group), but, in our opinion, because of the association of epigenetic loci in its gene with inflammation and CVD [ 37 ], CRP might become the “perpetrator and victim” of the same obesity-related DNA destabilization previously described [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 94%
“…A look-up analysis using the EWAS Catalog revealed that 1,496 associations (4.4%) from the basic model were previously reported in the literature 6,7,26,35,36 . Effect sizes for 1,379 significant CpG associations in the largest existing EWAS on CRP were correlated 97% with corresponding associations in our study 6 (Additional file 4: Fig.…”
Section: Epigenome-wide Association Study To Identify Individual Cpg ...mentioning
confidence: 85%
“…Methylation is most commonly observed at so-called CpG islands [ 3 ], which are long repeats of cytosine-guanine nucleotides. As technologies to study genome-wide DNA methylation continue to develop, there is growing evidence that there is a strong link between DNA methylation and CVD [ 4 6 ]. However, there is still little to no evidence of the directionality of this relationship, and clear findings on relevant CpG sites or genes have not yet emerged from the extensive research in this area.…”
Section: Introductionmentioning
confidence: 99%